(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Characteristics of frost- and winter resistance for some plant species of different origin from the NBG collection in the connection with the weather conditions during the winter 2012 have been given. The connection between the degree of the frost damages and microclimatic conditions of the growing territory, advective and radiational weather has been demonstrated. It has been found out that advective reduce of the air temperature to – 7,9…–90C united with the low air humidity and strong wind brought more considerable damages than radiational cooling to –100 С. ...–11,90 С. It has been determined that variegated forms of Euonymus japonicus, Вuxus sempervirens, Aucuba japonica are less resistant to the both - radiational and advective weather in the comparison with resistant forms. As the result of the correlation of frost damages intensity for the evergreen and deciduous introducted plants in the families Caprifoliaceae and Berberidaceae, data of their potential frost resistance and meanings of the equivalent-effective and real temperatures on the territory of NBG-NSC has been concluded that for most species advective weather is the most dangerous as this weather type contributes to the effective temperatures` reduce to the border level and even lower. Determination of the critical temperatures` borders for decorative introducted plants, meanings of the effective temperatures and probability of their coming are significant parameters for species assortment selection and park designing.